Covariation of Taxonomic and Functional Facets of β-diversity in Chilean Freshwater Fish Assemblages: Implications for Current and Future Processes of Biotic Homogenization - Castro-Morales, S; Rojas-Montecinos, P (Public Library of Science, 2023)
The biodiversity of assemblages that experience the introduction and extinction of species may lead to responses in two important facets: The taxonomic and functional diversity. The way in which these facets are associated may reveal important implications and consequences for the conservation of those assemblages. Considering the critical situation of freshwater fishes in continental Chile (30o – 56o S), we analyzed how the taxonomic (TDβ) and functional (FDβ) facets of β-diversity, and their components of turnover and nestedness, are associated. We evaluated changes in β-diversity (ΔTDβ and ΔFDβ), turnover (ΔTDtur and ΔFDtur), and nestedness (ΔTDnes and ΔFDnes) in 20 fish assemblages from their historical (pre-European) to current composition. We also simulated future trends of these changes, assuming that native species with conservation issues would become extinct. Our results show that the fish assemblages studied are in a process of loss of β-diversity, both in taxonomic and functional facets (ΔTDβ = -3.9%; ΔFDβ = -30.4%); also, that these facets are positively correlated in the assemblages studied (r = 0.617; P < 0.05). Both components showed by loss in nestedness (ΔTDnes = -36.9%; ΔFDnes = -60.9%) but gain in turnover (ΔTDtur = 9.2%; ΔFDtur = 12.3%). The functional β-diversity decreased more than the taxonomic (ΔFDβ > ΔTDβ), which was caused chiefly by six exotic species of Salmonidae, whose geographical spread was wider and that at the same time shared several morpho-functional traits. Our forecasts, assuming an intensification in the extinction of Endangered and Vulnerable native species, indicate that the process of homogenization will continue, though at a lower rate. Our study shows that the freshwater ichthyofauna of continental Chile is undergoing biotic homogenization, and that this process involves the facets of taxonomic and functional β-diversity, which are show high correlation between historical and current compositions. Both facets show that process is influenced by nestedness, and while turnover contributes to differentiation (both taxonomic and functional), its importance is overshadowed by nestedness. © 2023 Castro et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.